Attitudes Toward Statistics in students of grade of Pedagogy of the University of Barcelona - Ruth Vilà Baños; M.J. Rubio Hurtado (Universitat Politècnica de València, 2016)
The article presents the results of a study that measured the attitudes of students of Education of the University of Barcelona to the Statistics, through scale EAE by Auzmendi (1992). Research has shown neutral-low level of general attitude towards the matter, but has also identified groups of students with different profiles: a group with an attitude unfavorably, but not especially anxious, just knowledge of statistics and very few numerical skills; another group is characterized by a positive attitude, who like statistics, but that worry and anxiety also shows; and a third group that stands out above all for anxiety before statistics. Given the potential relationship between academic achievement andattitude, the findings point to the need to explore strategies for Adaptive education for different groups.